PENGEMBANGAN MODEL PEMBELAJARAN UNTUK PENINGKATAN KEMAMPUAN KOMUNIKASI LISAN SISWA - Lukman, _ (2016)
Reality,students who have graduated from junior high schools do not achieve the learning quality as expected by the curriculum. The alumni of junior high schools still have the low oral communication skill in English. The problem of the present research was what learning model which can improve the students' oral communication skill. The purpose of this research is to find a product in the form of learning model as an alternative learning model which can improve oral communication skill. The research approach used in this study was research and development by modifying the ten steps of research procedures into only three steps that are (1) preliminary study, (2) model development, and (3) model validation test. The participants of this study were the teachers and the students of the junior high schools in North of Lombok, Nusa Tenggara Barat. The data collection techniques used in this study were observation, questionnaire, document study, and oral test. The collected data were analyzed qualitatively and quantitatively (statistical test). This research and development study produced a learning model that can be used to improve the English oral communication skill. That learning model consists of five learning steps, namely (1)the orientation phase, (2) the phase of using command to direct behavior, (3) the phase of role reversal, (4) the phase of role independent practice, and (5) the phase of guided practice. After analyzing the data in the form score difference between pretest and posttest in the experimental group and the control group.It is concluded that the developed learning model effectively improved the junior high school students' spoken communication skill when being compared with the conventional learning model that was usually used by the teacher. The developed learning model emphasizes the students' activities in the learning process. It can be applied by the teacher through saying a word and demonstrating an act to represent its meaning without translating it into Language Indonesia, and asking the students to also demonstrate the word. After demonstrating the word, the students try to produce the oral language through the question and answer activities both independently and being guided by the teacher. Based on the findings, it is recommended for teachers, junior high school institutions, school committee, education department in local government, to utilize this learning model as an alternative model in learning English as an Foreign Language (EFL) in junior high schools. For further research, it is recommended to conduct the deeper and broader study correlated with the improvement of the students' English oral communication skill, especially in the context of implementing Total Physical Response and Direct Instruction learning models in junior high schools.;---Kenyataan di lapangan menunjukkan bahwa hasil pembelajaran bahasa Inggris di sekolah menengah pertama belum memenuhi kualitas pembelajaran yang diharapkan sesuai dengan tuntutan kurikulum.Lulusan sekolah menengah pertama masih lemah berkomunikasi lisan bahasa Inggris.Permasalahan dalam penelitian ini adalah model pembelajaran yang bagaimana yang dapat meningkat kemampuan komunikasi lisan siswa.Tujuan penelitian ini untuk menemukan suatu produk berupa model pembelajaran sebagai alternatif model pembelajaran yang dapat meningkatkan kemampuan komunikasi lisan. Pendekatan penelitian yang digunakan adalah penelitian dan pengembangan dengan memodifikasi sepuluh langkah pelaksanaan penelitian menjadi tiga langkah penelitian sebagai berikut: studi pendahuluan, pengembangan model, dan uji validasi model. Subjek penelitian ini adalah guru dan siswa sekolah menengah pertama di Kabupaten Lombok Utara Provinsi Nusa Tenggara Barat.Teknik pengumpulan data yang digunakan adalah observasi, angket, studi dokumentasi, dan tes lisan.Teknik analisis data yang digunakan adalah analisis kualitatif dan kuantitatif. Penelitian dan pengembangan ini menghasilkan model pembelajaran yang dapat meningkatkan kemampuan komunikasi lisan yang terdiri atas lima langkah pembelajaran, yaitu orientasi, bertukar peran, latihan mandiri, dan latihan terbimbing. Berdasarkan hasil analisis data perbedaan skor tes awal (Pretest) dan tes akhir (Posttest) pada kelompok eksperimen dan kontrol ditemukan bahwa model pembelajaran hasil pengembangan terbukti secara efektif dapat meningkatkan kemampuan komunikasi lisan siswa sekolah menengah pertama dibandingkan dengan pembelajaran konvensional yang dilakukan oleh guru selama ini.Hasil penelitian ini memberikan implikasi antara lain model pembelajaran hasil pengembangan menekankan aktivitas siswa dalam proses pembelajaran. Pembelajaran yang dilakukan guru dengan menggunakan bahasa Inggris sebagai bahasa pengantar ini dimulai dengan menyebutkan kosa kata tanpa menerjemahkan ke dalam bahasa Indonesia dan meminta siswa mendemonstrasikannya. Setelah mampu mendemonstrasikan kosa kata yang dipelajari, siswa berlatih memproduksi bahasa lisan melalui kegiatan tanya jawab baik secara mandiri maupun secara terbimbing. Bertolak dari hasil tersebut maka peneliti merekomendasikan kepada guru, kepala sekolah, dinas Dikpora, pengawas untuk menjadikan model pembelajaran ini sebagai salah satu alternatif model pembelajaran bahasa Inggris di SMP. Untuk peneliti selanjutnya disarankan agar melakukan kajian yang lebih mendalam dan meluas terkait peningkatan kompetensi komunikasi lisan bahasa Inggris siswa, khususnya dalam konteks implementasi model pembelajaran Total Physical Response dan Direct instruction di SMP.